An animal model further uncovers the role of mutant BrafV600E during papillary thyroid cancer development - Kölsch, Bernd; Theurer, Sarah; Staniszewska, Magdalena; Heupel, Jacqueline; Koch, Amelie; Mergener, Svenja; Walk, Franziska; Fischer, Christine; Kutritz, Andrea; Schmid, Kurt W.; Kindler-Röhrborn, Andrea (The American journal of pathology, 2020)
Papillary thyroid carcinomas (PTCs) account for 90% of human thyroid cancer cases, which represent 1% of all cancer cases. They are likely to develop from papillary thyroid microcarcinomas (PTMCs), found in up to 36% of healthy individuals, due to rare progression events (0.01%). Although the prognosis of PTCs is excellent, 5% to 10% of tumors display an unfavorable outcome. About 45% of PTCs exhibit activating BRAFV600E mutations. Rats of the inbred BD strains postnatally exposed to the carcinogen N-ethyl-N-nitrosourea developed PTMCs, which closely resembled their human counterparts judging from their histology, size, and marginal tendency to progress. DNA sequencing revealed mutations in exon 15 of the Braf gene identical to the human BRAFV600E mutation in 82% of the cases. Predominantly a 50:50 ratio of wild-type to mutant Braf alleles was seen regardless of tumor size or animal age, indicating that the Braf mutation is an early, if not the initial, event in rat PTMC development. Surprisingly, most PTMCs carrying a confirmed BrafV600E mutation did not display BrafV600E protein expression. As the BrafV600Egene is supposed to be the driver in PTC development, down-regulation of expression should contribute to the low risk for progression of PTMC. This model system will enable further insights into the molecular mechanisms of PTMC initiation and progression to PTC, further translating into targeted tumor prevention strategies/therapies.